Statistical techniques in business & economics : with global data sets - Lind, Douglas A.; Marchal, William G.; Wathen, Samuel Adam. (Boston : McGraw-Hill/Irwin, 2008)
All statistical concepts are illustrated with solved applied examples immediately upon introduction. Modern computing applications (Excel, Minitab and MegaStat) are introduced, but the text maintains a focus on presenting statistics concepts as applied in business as opposed to technology or programming methods. This book provides students majoring in management, marketing, finance, accounting, economics, and other fields of business administration with an introductory survey of the many applications and descriptive and inferential statistics.
Includes index.
obn 05/10/2018
Loans
Keywords: Statistical mathematics; Commercial statistics; Economics---Statistical methods; Social sciences---Statistical methods